2021
DOI: 10.3389/fnins.2021.651094
|View full text |Cite
|
Sign up to set email alerts
|

Subcommissural Organ-Spondin-Derived Peptide Restores Memory in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disease that affects millions of older people worldwide and is characterized by a progressive deterioration of cognitive functions, including learning and memory. There are currently very few approved treatments (i.e., acetylcholinesterase inhibitors such as donepezil), all of which are limited to the symptomatic control of AD and are associated with side effects that may result in discontinuation of treatment. Therefore, there is an urgent need to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Besides tryptophan and homocysteine, the PD analysis showed increasing and decreasing variations for the plasma levels of glutamine and glutamate, respectively, at 10 h in participants treated with NX210/NX210c (data not shown). Recently, studies demonstrated the neuroprotective action of NX210c against glutamate-induced excitotoxicity in primary rat cortical and hippocampal neurons, as well as human cortical neurons [ 9 , 10 ]. Interestingly, glutamate (a major excitatory neurotransmitter) is highly abundant throughout the brain; it plays a crucial role in neuronal plasticity and the maintenance of cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides tryptophan and homocysteine, the PD analysis showed increasing and decreasing variations for the plasma levels of glutamine and glutamate, respectively, at 10 h in participants treated with NX210/NX210c (data not shown). Recently, studies demonstrated the neuroprotective action of NX210c against glutamate-induced excitotoxicity in primary rat cortical and hippocampal neurons, as well as human cortical neurons [ 9 , 10 ]. Interestingly, glutamate (a major excitatory neurotransmitter) is highly abundant throughout the brain; it plays a crucial role in neuronal plasticity and the maintenance of cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to oxidation and the consequent formation of an intrachain disulfide bridge between the two cysteines, the peptide can take a cyclic conformation and is termed cyclic NX210 (NX210c). Preclinical in vitro and in vivo data have shown that NX210 exhibits important properties, which may be suitable for the treatment of neurological disorders in humans (i.e., neuroprotection, neuroregeneration, induction of remodeling and cellular plasticity mechanisms, and anti-neuroinflammatory action) [ 8 , 9 ]. This includes data showing that NX210/NX210c prevents glutamate-related cell death (excitotoxicity) in various primary neuronal cell types of human or rodent origin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been proposed that the progressive atrophy of human SCO with the subsequent lack of SCO-spondin may be contributing to the failure of human adult neurons to repair in CNS injuries or diseases [ 76 ]. In this way, a peptide derived from the first TSR domain of SCO-spondin protects neurons from glutamate-induced excitotoxicity [ 76 ] and restore learning and memory in a mouse model of Alzheimer’s disease [ 188 ].…”
Section: Discussionmentioning
confidence: 99%